The protective effect of Buzhong Yiqi decoction on ischemic stroke mice and the mechanism of gut microbiota - Li, Qianqian; Cao, Mengxin; Wei, Zijun; Mei, Jianing; Zhang, Yuechan; Li, Man; Li, Manlin; Zhang, Yunyun; Wang, Zhifei (Frontiers in Neuroscience, 2022)
The utilization of Buzhong Yiqi decoction develops effective interventions into preventing or reducing recurrence of ischemic stroke. Our research purports to provide experimental evidence for Buzhong Yiqi Decoction in the preventive treatment of ischemic stroke and to explore whether whose mechanism performance is through the medium of the gut microbiota on the methods of 16SR RNA and fecal microbiota transplantation. The results showed that prophylactic administration of Buzhong Yiqi Decoction could reduce the volume of cerebral infarction in MCAO mice, improve neurological function and behavior, and reduce apoptotic cells in the cortex around the infarction. Prophylactic administration of Buzhong Yiqi Decoction can regulate intestinal microbiota and increase the abundance of butyrate-producing Prevotellaceae_NK3B31_group and probiotic Akkermansia in mice 72h after a surgery. Transplanting Buzhong Yiqi Decoction-administered bacterial flora into antibiotic-depleted mice can reproduce the therapeutic effects of Buzhong Yiqi Decoction, including the reduction of cerebral infarction volume, the recovery of neurological function and behavior, as well as the diminution of apoptotic cells in brain tissue. Buzhong Yiqi Decoction administration can expand the abundance of Lachnospira_UCG-006, weaken the abundance of Streptococcus and norank_f__Erysipelas, and propagate the probiotics Lactobacillus and Butyricimonas. Our findings suggest that the preventive administration of Buzhong Yiqi Decoction has neuroprotective effects on ischemic stroke mice, and the mechanism of its effect may be related to the intestinal microbiota.